Growth in confinement promotes Pseudomonas aeruginosa tolerance to antibiotics - Sourabh Monnappa; Zainebe Al-Mayyah; Mahmut Selman Sakar; Alexandre Persat (Proceedings of the National Academy of Sciences, 2026)
Bacteria often proliferate within confined spaces imposed by host tissues, extracellular matrices, or their own biofilms where cells press against surrounding materials and experience elevated mechanical stress. Whether these forces influence pathogen physiology and fitness remains unresolved. We show that Pseudomonas aeruginosa adapts to mechanical confinement by increasing resilience to antibiotics. Using synthetic hydrogels of tunable stiffness that restrict expansion without limiting nutrient access, we demonstrate that growth in elastic materials reduces P. aeruginosa sensitivity to antibiotics in a stiffness-dependent manner. Although slower growth contributes to tolerance, Tn-seq under colistin and tobramycin treatment identified key regulators of mechanically induced tolerance. We found that active efflux mediated by sodium–proton Sha antiporters, together with protective remodeling of the bacterial membrane, enhances the resilience of confined populations without impacting growth. These findings reveal that P. aeruginosa adapts to mechanical stress in ways that may promote treatment failure even in the absence of intrinsic resistance.